2013
DOI: 10.1177/0748233712469995
|View full text |Cite
|
Sign up to set email alerts
|

Juniperus communis Linn oil decreases oxidative stress and increases antioxidant enzymes in the heart of rats administered a diet rich in cholesterol

Abstract: It has been asserted that consumption of dietary cholesterol (Chol) raises atherosclerotic cardiovascular diseases and that Chol causes an increase in free radical production. Hypercholesterolemic diet has also been reported to cause changes in the antioxidant system. In our study, different doses of Juniperus communis Linn (JCL) oil, a tree species growing in Mediterranean and Isparta regions and having aromatic characteristics, were administered to rats; and the levels of antioxidant enzymes superoxide dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Anti-diabetic and antichronic cystitis hyperlipidemic (Banerjee et al, 2013) ( Gumral et al, 2015) Antimicrobial activity (Pepeljnjak et al, 2005), antioxidant activity (Hoferl et al, 2014), Anti-hyper cholesterolemic activity (Akdogan et al, 2012) Neuroprotective (Bais et al, 2014a) Antibacterial activity (Sati and Joshi, 2010), anti-inflammatory (Tunon et al, 1995), anticataleptic activity (Bais et al, 2014b) Juniperus wallichiana NISCAIR/RHMD/ Tree (blue pine forest)…”
Section: Preparation Of Extractmentioning
confidence: 99%
“…Anti-diabetic and antichronic cystitis hyperlipidemic (Banerjee et al, 2013) ( Gumral et al, 2015) Antimicrobial activity (Pepeljnjak et al, 2005), antioxidant activity (Hoferl et al, 2014), Anti-hyper cholesterolemic activity (Akdogan et al, 2012) Neuroprotective (Bais et al, 2014a) Antibacterial activity (Sati and Joshi, 2010), anti-inflammatory (Tunon et al, 1995), anticataleptic activity (Bais et al, 2014b) Juniperus wallichiana NISCAIR/RHMD/ Tree (blue pine forest)…”
Section: Preparation Of Extractmentioning
confidence: 99%
“…Essential oils (EOs) obtained from this genus are extensively used in cosmetics, perfumery, pharmaceutical and in food additive industries . Literature survey revealed that Juniperus belongs to one of the potential biologically active species having antifertility, hypoglycaemic, antidiabetic, antifungal, diuretic, antiseptic, carminative, stomachic and antirheumatic activities .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that ISOinduced myocardial injury is mediated primarily via the β-adrenergic receptor. Acute β-adrenergic receptor stimulation not only leads to generation of reactive oxygen species but also depletes total cellular antioxidant capacity, downregulates copper-zinc SOD activity and reduces GSH level, leading to the loss of membrane integrity and induction of heart contractile dysfunction and myocyte toxicity, finally producing myocardial necrosis [36]. In the present study, these biochemical alterations were observed in ISO-treated rats.…”
Section: Discussionmentioning
confidence: 76%